The Effect Of Motivation And Perceived Risk On Purchasing Cosmetics Products - Jalalkamali, Mohammad (2008)

(untitled)
Kajian ini dilakukan untuk menyiasat pengaruh motivasi dan jangkaan ancaman terhadap keputusan pembelian barangan kosmetik di kalangan pelajar institusi pengajian tinggi. Dua dimensi motivasi yang telah dikaji adalah stimuli dalaman dan stimuli luaran. Enam komponen jangkaan ancaman yang dikaji adalah ancaman fizikal, ancaman pencapaian, ancaman kewangan, ancaman mas a, ancaman sosial dan ancaman psikologi. The purpose of this study is to find out the effect of motivation and perceived risk on purchase decision for cosmetics products among the university students. Two dimensions of motivation studied in this research are internal stimuli and external stimuli. Perceived risk has six components: physical risk, performance risk, time risk, psychological risk, financial risk and social risk.